Collaboration networks in economic science - Rose, Michael E (School of Economics, 2019)
When preparing a research article, Economists receive feedback from other academics, present on conference and give talks in seminars. This form of collaboration is termed informal because informal collaborators have, unlike authors, no formal property rights associated with their contribution. However, informal collaboration is so widespread that it appears to be part of the academic production function. Yet, it has received little attention in academia, least in Economics where patterns of informal collaboration differ from that of natural sciences. Social informal collaboration, the provision of direct feedback, gives rise to a social network. This thesis examines this network. The analysis focuses on the role of individual scientists in the network, which is estimated by different network centralities. Data originate from about 6000 published research articles from six Financial Economics journals between 1997 and 2011. A theoretical model describes how network centrality proxies the effort informal collaborators exert informally in a project, and how this improves the citation count of the research paper. We then investigate how observable characteristics of authors determine this and other centrality measures and find that common metrics such as productivity and number of citations correlate little with network centrality. As information transmission is an important aspect of social networks we study how network centrality of Economists relates to placement outcomes of their students in the academic job market. These findings suggest that even informal networks matter in the production of academic research; that these networks contain information above currently used measures of scholarly influence in the profession; and that these networks are used to decrease information asymmetry in the academic labor market.